臺灣西南海域岩心OR1-858-11地球化學特徵之研究 - 邱靖堯; Chiu, Chin-Yao (2011)
本研究對FATES計畫中從臺灣西南海域採取的一根具有很好的210Pb和137Cs定年之岩心，OR1-858-11(全長53 cm)，進行總有機碳(TOC)、氮(TON) 、和它們的δ13C、δ15N，以及無機沉積的碳酸鹽以及有孔蟲殼體（G. sacculifer）的δ18O分析。另外，對沉積物稀酸可溶相（0.5N HCl）中重金屬元素（Cu, Zn, Pb, Co, Ni, Cr）進行量測。這些地球化學的分析目的在計算高屏外海碳通量，並利用碳氮氧同位素、C/N變化趨勢重建這個區域過去百年來氣候與環境變化。 岩心經定年後其沉積時間從1884年到2007年，平均沉積速率約為0.279 g/cm2/yr。δ13C (PDB)平均值：-21.6‰，TOC平均值：0.83±0.06 wt%，TIC平均值：0.97±0.09 wt%，δ15N平均值：3.6 ‰，C/N值介於7-9之間，平均為7.76。沉積物中由有機碳和無機碳提供的通量為5.03 mg C/cm2/yr。 岩心的TOC、C/N、δ13C、δ15N結果顯示，有機物主要是海洋藻類，C/N主要反映TOC的變化。C/N在1940年後明顯升高，可能顯示陸源輸入增加，反映人類活動造成地表植被的破壞。1995年以前，有機碳、氮同位素在長時間趨勢上呈正相關，也說明有機物以海相生成為主，可能反映海洋初級生產力，在濕潤氣候條件下，河流營養鹽輸入增加，海洋初級生產力提高，δ13C和δ15N變重。而在1995年以後，有機碳、氮同位素呈負相關，推測可能受陸源有機質的影響。此外，在無機碳δ18O值除去有孔蟲的影響後，與高雄地區近七十年雨量有著良好對比，顯示Δδ18Ow與雨量間存在正相關性。 岩心在2000-2007年之間的沉積有濁流層出現，推測與颱風（如：海棠颱風）帶來龐大雨量造成陸源沉積物大量輸入到該岩心站位，造成從210Pb沉積序列擾動、δ13C變輕、C/N變低以及δ15N變重，也可能是改變陸源物質有機質的原因。這種事件在岩心過去百年的沉積中不多見，也許指示人類活動造成的植被退化、地表侵蝕加劇，值得警惕。 岩心沉積物稀酸可溶相中重金屬元素含量，銅：6.27 ~ 13.68ppm，鉛：11.72 ~ 23.07 ppm，鈷：4.57 ~ 9.95ppm，鎳：6.67 ~ 12.62ppm，鉻：3.83 ~ 7.48ppm，鋅：26.37 ~ 44.09ppm。整體變化趨勢在1960年以前變化不大，但在1960年後則有逐漸升高的趨勢，可能與高雄地區重工業發展有所關連。在1980年以後則有逐漸下降的趨勢，推測與環境改善有關。 A 53-cm long box core OR1-858-11 was collected from the southwest sea floor of Taiwan through the FATES project in 2008 The core had been well dated by 210Pb and 137Cs methods provided by Dr Chih-An Huh at the Institute of Earth Sciences of the Academia Sinica Using this well-dated core we have analyzed total organic carbon (TOC) total organic nitrogen (TON) and their δ13C and δ15N and δ18O of planktonic foraminifera (G sacculifer) and CaCO3 grain inorganically precipitated from surface seawater In addition we also measured heavy metal concentrations such as Cu Zn Pb Co Ni and Cr in 0 5N HCl leachable phase These geochemical analyses allow us to calculate the carbon fluxes and identify their sources in the southwest coast specifically in the Kaoping Submarine Canyon area and to reconstruct changes climate environmental of studying area during the past 100 years This core covers deposition from AD 1884 to 2007 and has an average deposition rate of 0 279 g/cm2/yr For a total of 53 subsamples from the core the average TOC and δ13CTOC (PDB) are 0 83±0 06 wt% and -21 6? respectively The δ15NTON averages 3 6 ? and the C/N ratio varies between 7 to 9 and averages 7 76 The total inorganic carbon (TIC) of the core has an average of 0 97±0 09 wt% Using these data we obtain a rough carbon flux (TOC+TIC) to the sediments in the studying area being 5 03 mg C/cm2/yr The TOC C/N δ13CTOC and δ15NTON results of the core indicate that (1) variations of the C/N ratio are chiefly controlled by the changes in TOC (2) Relatively heavy δ13C and δ15N and low C/N indicate that the organic matter is mainly from marine algae (3) The C/N ratio became higher after 1940 maybe reflecting increase of terrestrial input caused by deforestation due to human activities (4) Before 1995 δ13CTOC and δ15NTON showed a positive correlation and their values reflected mainly marine organic products When nutrient input from river increases under wetter climate conditions the marine primary productivity in the area increases so that δ13C and δ15N become heavier After 1995 δ13CTOC and δ15NTON exhibit a negative correlation suggesting significant terrestrial organic input We have measured the δ18O and δ13C of both total inorganic carbon (TIC) and planktonic foraminifera (G sacculifer) in the 53 subsamples from the core The average δ18O values of TIC and G sacculifer are -6 3±0 9? (PDB) and -2 2±0 2? (PDB) respectively The lighter δ18O values of TIC indicate that these carbonate grains formed in the surface water where the river water mixing is significant whereas the foraminifera shell formed in the shallow water of marine environment Using δ18O of TIC and G Sac and Kaohsiung air temperature we have calculated the δ18O difference of water masses for detecting river input A decrease in Δδ18Ow indicates an increase in river input resulted from rainfall increase The variation of the calculatedΔδ18Ow correlates with Kaohsiung rainfall during the past 70 years The core top appeared a turbulent layer between 2000 and 2007 such as result from Typhoon Haitang The enormous rainfall brought by typhoon might cause large terrestrial input to the core site The terrestrial sediments contain lighter δ13C and lower C/N However such an event was rare in the core during the past when typhoon always existed One explanation is that soil erosion became serious during the past decade because of vegetation degradation (or deforestation) under human activities We have measured the heavy metal elements in 0 5N HCl leachable phase of the sediments in the core Copper range between 6 27 ~ 13 68ppm; Lead range between 11 72 ~ 23 07 ppm; Cobalt range between 4 57 ~ 9 95ppm; Nickel range between 6 67 ~ 12 62ppm; Chrome range between 3 83 ~ 7 48 ppm; Zinc: range between 26 37 ~ 44 09ppm Before 1960 these elemental concentrations were relatively constant After 1960 the concentrations gradually increased perhaps related to the development of heavy industry in the Kaohsiung area After 1980 the elemental concentrations decreased suggesting the improvement of the environmental control